Development of Acoustic Insulating Carpets from Milkweed Fibers Using Air-Laid Spike Process - Deborah Lupescu; Mathieu Robert; Said Elkoun (Fibers)
Fibers from milkweed, which grows in Quebec (Canada), offer a distinct and outstanding advantage compared to other natural fibers: their ultra-lightweight hollow structure provides excellent acoustic and thermal insulation properties for the automobile industry. To highlight the properties of milkweed fibers and reduce the use of synthetic materials in vehicles, nonwoven carpeting made from a blend of milkweed fibers and polylactic acid (PLA) fibers was produced using the air-laid process. Some of the nonwovens were compressed to investigate the effects of increased mass per unit area on their thermal, acoustic, and mechanical properties. The nonwovens’ mass per unit area, thermal insulation, sound absorption coefficient, airflow resistivity, compression, and resistance to moisture were evaluated and compared to other carpets made of natural and synthetic fibers. The findings indicate that milkweed and PLA carpets have lower thermal conductivity values of 37.45 (mW/m·K), (mW/m·K) less than carpets made from cotton and polypropylene. At low frequencies, none of the carpets absorbed sound. At high frequencies, milkweed and PLA carpets showed sound absorption values of at least 0.6, which provide better acoustic insulation than nonwoven materials made from jute and polyethylene (PE) fibers. Milkweed and PLA carpets exhibited better compression values than polypropylene (PP) carpets.